Merger dan Akuisisi: Sebuah Perkawinan Paradoksal - Achmad Sobirin (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2001)
From human and cultural perspectives, it can be said that merger and aquisition (M&A) is a kind of paradoxal marriage. While its main objective is to create synergy, the reality shows it differently. Many companies that decided to enter into M&A fail to achieve its objective particularly due to human and cultural problems. Therefore, to prevent, or at least, to minimize these problems, the companies should prepare psichologically, understand each others, and conduct due dilligent including human and cultural audit before entering into the marriage. This is what this paper is trying to discuss. By discussing this topic it is expected that human and cultural variables being neglected so far, are to be considered into the M&A’s decision so that the implementation of the marriage can be run smoothly.Keywords : merger & acquisition ( M & A), paradoxal marriage, open marriage, traditional marriage, modern marriage